Investigation of E-Capacity for Biometric Identification Protocol with Random Parameter - Haroutunian, Mariam E.; Ter-Vardanyan, Lilit A. (Mathematical Problems of Computer Science, 2021)
In recent years biometrics is widely used in different tasks in the field of security. In this paper we investigated the biometric identification system from an information theoretical point of view. We investigate the exponentially high reliability criterion in biometric identification systems. The biometric identification system with random parameter is considered, which is more realistic for application. The lower and upper bounds of identification E-capacity of the model with random parameter for maximal and average error probabilities are constructed. When E → 0 we derive the corresponding bounds of the capacity of the biometric identification system with random parameter, which coincide and hence, as a corollary we obtain the identification capacity for this model.